Do Unilateral Trade Preferences Help Reduce Poverty in Beneficiary Countries? - Sèna Kimm Gnangnon (ZBW - Leibniz Information Centre for Economics, 2021)
This paper has investigated the utilization of non-reciprocal (or unilateral) trade preferences (NRTPs) provided by QUAD countries on poverty in recipient-countries. It uses a panel dataset of 77 beneficiaries of NRTPs over the period of 2002-2019, and considers two main blocks of NRTPs, namely 'Generalized System of Preferences' (GSP) programs and 'other trade preferences programs'. The analysis relies on two main indicators of poverty, i.e., the poverty headcount ratio at 1.90 and the poverty gap at 1.90, but also provides a robustness check using indicators of poverty at 3.20 and 5.50. Empirical findings obtained from the use of the two-step generalized methods of moments indicate that over the full sample, an increase in the utilization rates of both GSP programs and other trade preferences programs is associated with poverty reduction in beneficiary countries, with the magnitude of this effect being higher for least developed countries (LDCs) than for other countries in the full sample. Additionally, GSP programs and other trade preferences programs are strongly complementary in helping reduce poverty in beneficiary countries. Finally, the effect of the utilization of each type of NRTPs on poverty works through the economic complexity channel, as the greater the level of economic complexity, the higher is the negative effect of the utilization of these NRTPs on poverty.
Keywords: F13; F14; O14; 330; Utilization of non-reciprocal trade preferences; Poverty; QUAD countries; Beneficiary countries